please help

The midpoint (x, y) and the end point (x2, y2) are known. Find (x1, Y1) using the midpoint formula.

a. (x1,y1) = (2x + x2, 2y+y2)

b. (x1,y1) = (2x - x2, 2y - y2)

c. (x1,y1) = (x + x2, y + y2)

d. (x1,y1) = (x - x2, y - y2)

Respuesta :

Thdev

Answer:

B

Step-by-step explanation:

So this was a pretty difficult question to do algebraically so I just came up with an example.

Ver imagen Thdev

Step-by-step explanation:

Hey,there!!!

Let's simply work with it,

We have,

One point is (x2,y2) and midpoint is(x,y).

Now, let's use midpoint formulae,

[tex](x ,\: y) = \frac{x1 + x2}{2} + \frac{y1 + y2}{2} [/tex]

Now, let's equate with their corresponding elements we get,

[tex]x = \frac{x1 + x2}{2} [/tex]

now, 2x=x1+x2

or, x1=2x-x2

and

[tex]y = \frac{y1 + y2}{2} [/tex]

now,

2y = y1+y2

or, y1 = 2y-y2

Therefore, the answer is (x1,y1)= { (2x-x2),(2y-y2) }

Hope it helps...